Activities of territorial bodies of the NKVD in Far East providing road safety in 1941–1945 - A. V. Zhadan (Омский научный вестник: Серия "Общество. История. Современность")
The publication is devoted to a little–studied aspect of the activities of the internal affairs bodies of the Far East during the Great Patriotic War - providing road safety. The basis of the work is unpublished sources related to the official and party documentation of the regional departments of the NKVD of the Khabarovsk and Primorsky Territories. The methodological basis of the research is the principles of historicism and consistency, as well as general scientific historical and logical methods. The article describes the situation in the field of road safety in the Far East during the period under study, analyzes the causes and conditions of its deterioration, the measures taken by the internal affairs bodies to normalize the operational situation.